The analysis of disease spectrum of traditional Chinese medicine of outpatient visitor to the contracted family doctor in Shenzhen community health centers - Zhaoxia Yin; Chongyu Kong; Xianhui Zou; Chuang Li; Yin Huang; Yang Feng; Yunfei Wang; Weijie Gong (Chinese General Practice Journal)
Background: The development plan of traditional Chinese medicine (TCM) has been integrated into the national development strategy, with a focus on significantly enhancing the TCM service capabilities of primary care facilities. However, researches on the disease spectrum of TCM diagnosis and treatment in community health centers is lacking. Objective: To understand the TCM diagnosis and treatment capabilities of Shenzhen's community health centers by analyzing the disease spectrum of TCM diagnosis and treatment among outpatients signed with family doctors at these centers. Methods: From May to June 2022, records of family doctor-signed residents who visited the outpatient departments of community health centers in 10 districts of Shenzhen from January 1, 2021, to June 30, 2021, and incurred diagnosis and treatment costs were extracted from the “Hangchuang Community Health Service Center Business System,” a unified information platform of the Shenzhen Health Commission. Records for which TCM was the purpose for the visit, which had corresponding diagnosis and treatment costs, as well as a primary diagnosis coded according to the “Classification and codes of diseases and patterns of traditional Chinese medicine” (TCD) were included in the study (n=385,138). The disease spectrum was analyzed based on the TCD, mainly involving specialty category, sub-specialty system classification and TCM term of disease and pattern. Results: Among the 385,138 records included, there were 170,077 male visits (44.16 %) with an average age of 37.5 ± 8.2 years; and 215,061 female visits (55.84 %), with an average age of 36.7 ± 9.4 years. The disease spectrum covered all seven specialty categories of TCD: internal medicine (219,445, 56.98 %), pediatrics (79,201, 20.56 %), otorhinolaryngology (47,965, 12.45 %), gynecology (30,620, 7.95 %), surgery (5,797, 1.51 %), orthopedics (1,407, 0.37 %), and ophthalmology (703, 0.18 %). The spectrum covered all sub-specialty system classifications under the seven specialty categories except for tumor diseases, cancer diseases in each specialty category, and certain eye disease classes such as diseases of the canthus, diseases of the cornea, pupil diseases, and traumatic eye diseases. In each specialty category, several diseases accounted for ≥90.00 % of the total diagnostic and treatment volume for that specialty category. The top five system diseases were respiratory system diseases (208,701, 54.19 %), musculoskeletal system diseases (73,369, 19.05 %), gynecological system diseases (30,620, 7.95 %), cardiovascular and cerebrovascular system diseases (27,539, 7.15 %), and digestive system diseases (19,162, 4.98 %). Patients under 15 and those aged 15 to 24 primarily had diseases related to the respiratory system and digestive systems. As age increased, the number of patients with paralysis, dizziness, headache, insomnia, and fatigue gradually increased; before the age of 45, the leading disease was the common cold, and after 45, it was muscle and joint pain caused by paralysis. Conclusion: The TCM diagnosis and treatment disease spectrum at Shenzhen's community health centers is broad but concentrated and singular, predominantly involving internal medicine. The disease spectrum is mainly concentrated in five major systems: respiratory, musculoskeletal, gynecological, cardiovascular and cerebrovascular, and digestive systems. There is a need to further enhance and expand the TCM diagnosis and treatment capabilities of community health centers to better meet the diverse health needs of residents.